Gasification performance of Spirulina microalgae – A thermodynamic study with tar formation. (1st April 2019) - Adnan, Muflih A.; Xiong, Qingang; Hidayat, Arif; Hossain, Mohammad M.
Highlights: A novel microalgae ( Spirulina) biomass gasification process is investigated. The process performance was studied with various char, O2 and steam flows. Tar can be completely gasified by adjusting the gasifying agents (O2 /steam) The introduction of optimization zone enhances concentrations of CO and H2 . Abstract: In this work, the performance of a novel configuration for Spirulina microalgae gasification was investigated through an improved thermodynamic model using Aspen Plus. Compared with existing thermodynamic models, tar formation is included in the improved counterpart. The proposed novel gasification process consists of four primary zones: (i) pyrolysis, (ii) combustion, (iii) gasification, and (iv) optimization. First, the modeling results were compared against experimental values, where a good agreement (relative error < 10%) was obtained under identical operating conditions. Then, performance of the novel gasification configuration was studied using the developed improved thermodynamic model at various operating conditions. Metrics such as gasification system efficiency, syngas composition and cold gas efficiency were used to measure the performance. It was found that incorporation of the optimization zone improves the concentration of CO and H2 at the controlled use of gasifying agents. Moreover, injection of suitable amount of gasifying agents enhances the gasification performance. Finally, the effects of O2 equivalence ratio and steam injection on the system performance were investigated.